Embryonic and larval development of the striped mullet Mugil cephalus (L) - Abraham, Mathew; Shiranee, P; Chandra, P Kishore; Kailasam, M; Charles, V K (Indian Journal of Fisheries, 2011)
Mugil cephalus in ripe condition collected from inshore catches at Muttukadunear Madras were induced to breed using HCG and ovaprim to study theembryonic and larval development. Samples of unfertilised eggs and variousdevelopmental stages from fertilization through embryonic and larval stageswere preserved for further micrographic studies. Rate of fertilization wasdetermined at the time of blastodisc formation and was 90 %. Of the totalnumber of 1.46 million eggs, 1.26 million were fertilised. The pre-hatchedembryo was deeply pigmented, exhibited twitching movements and lay curvedover the yolk mass. After an incubation period of 30-32 hrs, the embryo hatchedout. The newly hatched out larvae measuring 2.29 mm, were transparent witha large oval head, a well defined yolk sac and short tail encircled by acontinuous finfold. Mouth formation was complete and the larvae startedfeeding on 3rd day of hatching. The paper presents the results of detailedstudies of embryonic and larval development and the time scale establishedfor critical stages of development.